The Sensitivity of the Marine Carbonate System to Regional Ocean Alkalinity Enhancement - Burt, Daniel J.; Fröb, Friederike; Ilyina, Tatiana (Frontiers in Climate, 2021)
Ocean Alkalinity Enhancement (OAE) simultaneously mitigates atmospheric concentrations of CO2 and ocean acidification; however, no previous studies have investigated the response of the non-linear marine carbonate system sensitivity to alkalinity enhancement on regional scales. We hypothesise that regional implementations of OAE can sequester more atmospheric CO2 than a global implementation. To address this, we investigate physical regimes and alkalinity sensitivity as drivers of the carbon-uptake potential response to global and different regional simulations of OAE. In this idealised ocean-only set-up, total alkalinity is enhanced at a rate of 0.25 Pmol a-1 in 75-year simulations using the Max Planck Institute Ocean Model coupled to the HAMburg Ocean Carbon Cycle model with pre-industrial atmospheric forcing. Alkalinity is enhanced globally and in eight regions: the Subpolar and Subtropical Atlantic and Pacific gyres, the Indian Ocean and the Southern Ocean. This study reveals that regional alkalinity enhancement has the capacity to exceed carbon uptake by global OAE. We find that 82-175 Pg more carbon is sequestered into the ocean when alkalinity is enhanced regionally and 156 PgC when enhanced globally, compared with the background-state. The Southern Ocean application is most efficient, sequestering 12% more carbon than the Global experiment despite OAE being applied across a surface area 40 times smaller. For the first time, we find that different carbon-uptake potentials are driven by the surface pattern of total alkalinity redistributed by physical regimes across areas of different carbon-uptake efficiencies. We also show that, while the marine carbonate system becomes less sensitive to alkalinity enhancement in all experiments globally, regional responses to enhanced alkalinity vary depending upon the background concentrations of dissolved inorganic carbon and total alkalinity. Furthermore, the Subpolar North Atlantic displays a previously unexpected alkalinity sensitivity increase in response to high total alkalinity concentrations.